Agro Awareness at the Primary Stage - Nikalje, Varada Mohan; D, Radhika (THE PRIMARY TEACHER, 2018)
There is a growing concern worldwide that young people have become disenchanted with agriculture. This is all the more worrying because humanity needs more food in the foreseeable future, due to the rapid increase in the world population. In developing countries where agriculture is likely to provide the main source of income in a majority of households, it is vital that young people are connected with farming. In India, agriculture, with its allied sectors, is the largest source of livelihood. About 70 per cent of India’s rural households still depend primarily on agriculture for their livelihood, with 82 per cent of farmers being small and marginal. However, with growing urbanisation, more education, and the development of skills, the younger generation is moving away from agriculture. It is not simply a shift from rural to urban areas; there is a shift in mindset as well. A short survey conducted by the author indicates that young learners at the primary stage of schooling did not find agriculture appealing as a means of livelihood. The paper focuses on how such perceptions had been formed and states that a positive perception of agriculture can be strengthened in the next generation right from the primary stage of education. This would enable young learners to view farming, and allied areas, as desirable professions. The younger generation with a positive outlook towards agriculture would learn the traditional methods of farming and then may find ways to combine them with new technologies to get optimum results.